Factors Influencing Retirement Preparation (Study Case Pamulang University) - Diana Riyana Harjayanti; Angga Rovita; Ifa Nurmasari; Dony Oktariswan (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Individuals are expected to have adequate preparation to face retirement. Financial literacy can provide important information for individuals to plan for retirement. This study will examine social demographics (age, education, income, gender), financial literacy level, individual attitudes and behaviors and their impact on retirement preparation represented by lecturers at Pamulang University. One profession that is considered to have good financial literacy is lecturers. Therefore, it is expected that lecturers have good knowledge and understanding of financial planning, investment and retirement preparation. This study uses quantitative research methods. This study conducted a questionnaire survey using a sample of lecturers at Pamulang University, South Tangerang, Indonesia. Data processing using SPSS then using multiple linear regression tests, significant tests and obtained results that social demographics (age, education, income, gender), financial literacy has no significant effect on retirement planning. While individual attitudes and behaviors have a significant effect on retirement planning.